2021
DOI: 10.1093/mnras/stab1256
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-2D modelling of heat redistribution through H2 thermal dissociation/recombination: consequences for ultra-hot Jupiters

Abstract: Thermal dissociation and recombination of molecular hydrogen, H2, in the atmospheres of ultra-hot Jupiters (UHJs) has been shown to play an important role in global heat redistribution. This, in turn, significantly impacts their planetary emission, yet only limited investigations on the atmospheric effects have so far been conducted. Here we investigate the heat redistribution caused by this dissociation/recombination reaction, alongside feedback mechanisms between the atmospheric chemistry and radiative trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…For instance, for CoRoT-1 b, the terminator is found to be hotter than the dayside. While our results have large uncertainties, our study cannot confirm that the dissociation and recombination of H 2 have large effects on the day-terminator contrast (Tan & Komacek 2019;Roth et al 2021), as demonstrated in other observational studies. To our knowledge, the only planet for which such effect has been reported is KELT-9 b (Mansfield et al 2020b), but given the ) between 1 bar and 0.01 bar, which is around the region probed by the observations.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…For instance, for CoRoT-1 b, the terminator is found to be hotter than the dayside. While our results have large uncertainties, our study cannot confirm that the dissociation and recombination of H 2 have large effects on the day-terminator contrast (Tan & Komacek 2019;Roth et al 2021), as demonstrated in other observational studies. To our knowledge, the only planet for which such effect has been reported is KELT-9 b (Mansfield et al 2020b), but given the ) between 1 bar and 0.01 bar, which is around the region probed by the observations.…”
Section: Resultscontrasting
confidence: 90%
“…(3) What is the dayside-terminator contrast in exoplanet atmospheres? Planetary atmospheres present vertical and horizontal inhomogeneities: This is particularly true for tidally locked planets, for which large day-night thermal gradients, sometimes in excess of 1000 K, and asymmetric circulation patterns have been predicted (Cho et al 2003;Showman et al 2010;Cowan & Agol 2011;Roth et al 2021). Recent simulations using pseudospectral methods (Skinner & Cho 2021aCho et al 2021) have revealed the complex and turbulent nature of these atmospheres, displaying highly dynamic small-and largescale storms that develop and evolve in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining the scatter plot for overall trends, we see that the T day /T irr value of TOI-2109b lies in between the average value of the cluster of gas giants with T eq ∼ 3000 K, which are consistent with extremely low levels of daynight heat recirculation, and the lower value of KELT-9b. This behavior suggests a tenuous decreasing trend that is predicted by recent atmospheric modeling of ultrahot Jupiters, which has demonstrated that the dissociation of molecular hydrogen on the hot dayside and its recombination on the cooler nightside can efficiently transport energy across the planet's surface, resulting in lower dayside temperatures and reduced day-night tem-perature contrasts in the hottest exoplanets (e.g., Bell & Cowan 2018;Komacek & Tan 2018;Parmentier et al 2018;Tan & Komacek 2019;Roth et al 2021).…”
Section: The Atmosphere Of Toi-2109bmentioning
confidence: 71%
“…When examining the scatter plot for overall trends, we see that the T day /T irr value of TOI-2109b lies in between the average value of the cluster of gas giants with T eq ∼ 3000 K, which are consistent with extremely low levels of day-night heat recirculation, and the lower value of KELT-9b. This behavior suggests a tenuous decreasing trend that is predicted by recent atmospheric modeling of ultrahot Jupiters, which has demonstrated that the dissociation of molecular hydrogen on the hot dayside and its recombination on the cooler nightside can efficiently transport energy across the planet's surface, resulting in lower dayside temperatures and reduced day-night temperature contrasts in the hottest exoplanets (e.g., Bell & Cowan 2018;Komacek & Tan 2018;Parmentier et al 2018;Tan & Komacek 2019;Roth et al 2021).…”
Section: The Atmosphere Of Toi-2109bmentioning
confidence: 72%